Management dilemma of a child with long-segment tracheal stenosis, double outlet right ventricle, and left pulmonary artery sling: For single or staged repair? - Gurpreet Singh; Anna Marie Nathan; Norazah Zahari; Khairul Anuar Bin Abdul Aziz (Annals of Pediatric Cardiology)
This is a case of a 3-year-old child who presented with long-segment tracheal stenosis (LSTS) and complex congenital cardiovascular disease for surgical intervention. The ideal operation for this child will include slide tracheoplasty and multiple cardiac lesion repairs. However, the low birth weight and extremely young age present a dilemma as to whether to perform total repair simultaneously or in stages. Age and weight by which the first surgical procedure was done, cardiovascular abnormality details, preoperative respiratory support, preoperative tracheobronchomalacia, cardiopulmonary bypass, the complexity of the surgery, and preoperative extracorporeal membrane oxygenation support are known to be predictive factors of long-term outcomes. Comparative studies between simultaneous and staged operations have shown that it is best to manage children with LSTS and complex cardiovascular anomalies in stages.